Limits on WIMP dark matter using sapphire cryogenic detectors - Jochum, J; Angloher, G; Bucci, C; Cooper, S; Cozzini, C; DiStefano, P; von Fellitzsch, F; Frank, T; Hauff, D; Jagemann, T; Keeling, R; Kraus, H; et al. (2003)
Data taken by CRESST with a cryogenic detector system based on 262 g sapphire crystals has been used to place limits on WIMP dark matter. The experiment was especially sensitive for low-mass WIMPs with spin-dependent cross sections and improves on existing limits in this region.